Streptococcus dysgalactiae Septic Arthritis of a Pre-Weaned Holstein Bull Calf - a Case Report - Setiawan, Vincent; Raisatulhaq, Raida; Septiyani (Media Kedokteran Hewan, 2024)
Septic arthritis is a joint inflammation caused by an infectious agent. Septic arthritis takes a long time to heal, and as such it may have a significant economic impact. A one-month-old Friesian Holstein calf was lame and had swelling in the left carpal joint. Synovial fluid samples from the left carpal joint were used for bacterial identification, which use API Strept 20 (bioMérieux, Inc – USA). The identification results showed that septic arthritis was caused by Streptococcus dysgalactiae subspecies dysgalactiae,. Streptococcus dysgalactiae subspecies dysgalactiae play a significant role even though it plays a major role in mastitis in dairy cows.